Optimal selection of high-production well targets for fault-controlled fractured-vuggy reservoir in Shunbei oil and gas field, Tarim Basin - Lijun GAO; Haiying LI; Wei GONG; Wei YANG; Hongyan LI (Shiyou shiyan dizhi)
After years of exploration and development in the Shunbei oil and gas field, Tarim Basin, a series of technologies for ultra-deep fault-controlled fractured-vuggy target prediction, evaluation, and well location design have been formed, applicable to the No.1 and No.5 fault zones. As exploration efforts shift from the main No.1 and No.5 fault zones to the northeastern and northwestern fault zones in the eastern and western regions, the underground geological conditions become more complex, and exploration costs rise significantly. Existing reservoir characterization, target selection, and well trajectory design technologies are inadequate for the precise delineation of ultra-deep fault-controlled fractured-vuggy systems and high-yield well trajectory optimization. Through comparative analysis of the internal structural characteristics and seismic response variations of different regions and different types of strike-slip fault zones, integrated with actual well seismic calibration statistics and forward modeling, this study established a robust seismic identification model for high-yield and stable production wells. This model, based on the "source-connected faults + bead-string + deep chaotic high-amplitude background", provided a systematic framework for reservoir prediction and target selection. The Q-compensation seismic data processing technology developed through research improved the imaging resolution of fault-controlled fractured-vuggy systems in low signal-to-noise ratio seismic data under desert environments. Based on this, a reservoir quantification sculpting and target spatial positioning technology, centered on "facies-constrained inversion, " was established, which improved the accuracy of fault-controlled reservoir description and the precision of target selection. In response to the complex geological conditions of the overlying strata and Ordovician target layers in the Shunbei area, as well as challenges such as loss, overflow, and wellbore collapse during drilling, a key integrated geological engineering technology process focused on drilling risk prediction was established. This process included methods for optimizing well trajectories, selecting well locations, predicting formation pressures before drilling, and predicting wellbore stability, which improved drilling safety and efficiency. Drilling results from Shunbei's No. 4 and No. 8 fault zones indicated that the target selection and design technology for fault-controlled reservoirs could accurately identify and predict ultra-deep heterogeneous fractured-vuggy body targets, guide and optimize drilling trajectory design, avoid and reduce engineering risks along the drilling path, and improve the drilling success rate and high-yield well construction rate for large-scale reservoirs.